The involvement of B40 entrepreneurs in E-commerce: experience from Malaysia - Abd. Hadi, Fatimah-Salwa; Gan, Pei Tha; Zulkifli, Normala; Ismail, Zuriadah; Romli, Nurhanani; Ahmad, Mohamad Azahari; Mohd Thas Thaker, Mohamed Asmy; Ahmad Zaidi, Mohamad Faizal (Science and Engineering Research Support Society, 2020)
The focus of the study was: first; to identify the involvement of B40 entrepreneurs in e-commerce and, second; to analyse the factors influencing their involvement. This quantitative study involved 207 respondents chosen using the snowball sampling technique. All respondents were low-income government sector workers (B40) who were conducting business part-time to increase their income. Information was acquired via questionnaires which had been adapted according to the study’s suitability and adopted from several sources. The finding showed that the respondents were wellinformed about the existence of e-commerce. A majority of them only utilised e-commerce for shopping purposes and not for selling purposes even though they had products to be marketed. As for the respondents who sold products online, the most critical factors influencing their involvement were the income increase, broadband facility and knowledge about e-commerce. Regarding the respondents who did not market their products online, the critical factors which influenced them were the satisfaction of doing business in a traditional way, online business safety and lack of knowledge in handling online business were critical factors which hindered their involvement in e-commerce. As such, the B40 entrepreneurs were encouraged to make use of e-commerce to expand the market. They should also attend related courses, become mentee for successful e-commerce mentors, and strive to expand their business network. The huge investment made by the government to provide broadband facility for the community members should be fully utilised especially by the B40 entrepreneurs in their effort to increase their income level.